Protoperidinium sphaericum (G. Murr. et Whitting) Balech 1974 (История изучения, морфология, синонимика) - Крахмальный, А.Ф.; Зареи-Дарки, Б. (Альгология, 2017)
Изучена морфология редкого вида морских динофлагеллят Protoperidinium spaericum (Dinoflagellata, Dinophyta), обнаруженного в планктоне Персидского залива у о-ва Ормуз (территориальные воды Ирана). Установлена морфологическая идентичность P. spaericum, P. hamatum Balech 1979, найденных ранее в Персидском заливе и P. sphaeroides (Dangeard) Balech 1974, известного только для Средиземного моря. Учитывая литературные и оригинальные данные, в соответствии с принципом приоритета, предложено считать P. hamatum и P. sphaeroides синонимами P. sphaericum. Уточнено распространение P. sphaericum: Средиземное, Адриатическое и Карибское моря, Мексиканский, Персидский и Оманский заливы, юго-западная Атлaнтика, прибрежные воды западной Африки и Японии. This paper reveals the morphological study of Protoperidinium sphaericum, a rare species of marine dinoflagellates (Dinoflagellata, Dinophyta) found in the plankton of the Persian Gulf near the island of Ormuz (territorial waters of Iran). The study proved the morphological identity of P. spaericum, P. hamatum Balech 1979, found earlier in the Persian Gulf, and P. sphaeroides (Dangeard) Balech 1974 known only from the Mediterranean Sea. After analyzing the literature and original data, and in accordance with the principle of priority, P. hamatum and P. sphaeroides are considered synonymous with P. sphaericum. The range of P. sphaericum includes Mediterranean, Adriatic and Caribbean Seas, Mexican, Persian and Oman Gulfs, Southwest Atlantic, and the coastal waters of west Africa and Japan.